Reproducing Computerised Picture (RCP) Using Rotated Ordered-Dither Matrix - Mohd Kasirun, Zarinah (Malaysian Journal of Computer Science, 2017)
Reproducing Computerized Picture (RCP) is a windowsbased system that can be used to convert pictures with multi-level intensities into a continuous gray-scale intensity of pictures. RCP has shown that a rotated ordered-dither matrix would produce an output much better than the usual ordered-dither matrix for .BMP files. With the successful development of RCP, it will overcome the main problem of some devices, which can only display two levels of intensity, i.e., black and white.